Leaching SiO₂ On Coal Fly Ash As Ammonium Adsorbent In Tofu Liquid Waste Using Hydrothermal Method - Danang Jaya; Anisa Anisa; Dian Prasetyani Basuki; Tunjung Wahyu Widayati (Eksergi, 2022)
Soybean is one of the main food commodities in Indonesia. One of the soybean processing that is often consumed is tofu. Inappropriate treatment of tofu liquid waste is very dangerous for life. It is noted that the ammonia content in tofu liquid waste is 23.3-23.5 mg/l which can cause odors that disturb the residents' comfort. One alternative solution for purifying tofu liquid waste is to carry out an adsorption process using coal fly ash. Fly ash contains metal oxides in the form of SiO₂, Al₂O₃, Fe₂O₃, CaO, MgO, K₂O, and Na₂O. The content of SiO₂ as much as 60-70% in it causes fly ash to be very potential to absorb ammonia levels. Extraction of SiO₂ using the sol gel method was carried out using fly ash that had gone through a hydrothermal process. The hydrothermal process is a crystallisation technique in a closed container with high temperature and pressure. After going through the extraction stage, the ongoing process was continued with the washing stage to produce silica powder to adsorb ammonium. The mass required for silica to achieve the optimum ammonia concentration adsorption efficiency is 0.25 gram/20 ml of tofu liquid waste. Meanwhile, the contact time required for silica to achieve the optimum adsorption efficiency of ammonium content is 30 minutes. It was noted that the silica from the optimised fly ash processing had a better quality than the unoptimized silica or commercial silica.